1993
DOI: 10.1136/bmj.307.6896.92
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in offspring of hypertensive parents.

Abstract: Objective-To determine if insulin resistance is present in normotensive adults at increased risk ofdeveloping hypertension.Design-Normotensive subjects with at least one hypertensive parent were paired with offspring of normotensive parents (controls), being matched for age, sex, social class, and physical activity.Setting-Outpatient clinic. Subjects-30 paired subjects (16 men and 14 women) with and without a family history of hypertension, aged 18-32, with a body mass index < 25 kg/mi, with blood pressure < 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(65 citation statements)
references
References 40 publications
2
57
1
5
Order By: Relevance
“…The existence of early abnormalities of glucose and insulin metabolism among offsprings of hypertensive parents has been confirmed by some investigators, 7,19,[24][25][26] although not by all. 15,27 Previous studies have shown elevated fasting insulin and insulin-to- Early abnormalities in family hypertension EG Ciolac et al glucose levels, as well as reduced sensitivity of insulin-mediated cellular glucose disposal, in normotensive offspring of hypertensive parents; however, data have not been analysed separately by neither gender nor parental burden.…”
Section: Lipids Glucose and Insulinmentioning
confidence: 95%
See 2 more Smart Citations
“…The existence of early abnormalities of glucose and insulin metabolism among offsprings of hypertensive parents has been confirmed by some investigators, 7,19,[24][25][26] although not by all. 15,27 Previous studies have shown elevated fasting insulin and insulin-to- Early abnormalities in family hypertension EG Ciolac et al glucose levels, as well as reduced sensitivity of insulin-mediated cellular glucose disposal, in normotensive offspring of hypertensive parents; however, data have not been analysed separately by neither gender nor parental burden.…”
Section: Lipids Glucose and Insulinmentioning
confidence: 95%
“…15,27 Previous studies have shown elevated fasting insulin and insulin-to- Early abnormalities in family hypertension EG Ciolac et al glucose levels, as well as reduced sensitivity of insulin-mediated cellular glucose disposal, in normotensive offspring of hypertensive parents; however, data have not been analysed separately by neither gender nor parental burden. 7,[24][25][26] The only study we have known that assayed fasting insulin and insulin resistance in normotensive with three different parental hypertension burden showed that normotensive offspring of two hypertensive parents had elevated plasma insulin levels and were more likely to show greater insulin resistance than normotensive individuals having either one hypertensive parent or normotensive parents; however, the data were also not analysed separately by gender. 19 This study demonstrated that insulin and insulin-toglucose ratio (a marker of insulin resistance) were higher in both women with two or one hypertensive parents than in women with normotensive parents, when a population of young normotensive women matched for age, menstrual cycle phase, BMI and BP levels were analysed.…”
Section: Lipids Glucose and Insulinmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin-mediated glucose uptake is reduced by 30 -40% in people with essential hypertension (Ferrannini et al, 1987), an abnormality demonstrated in both non-obese and obese individuals with hypertension (Reaven, 1991) and in young normotensive subjects who are at increased risk of developing hypertension (Beatty et al, 1993). Furthermore, this abnormality continues to be present even after the hypertension has been treated effectively (Reaven, 1991).…”
Section: Other Features Of the Metabolic Syndromementioning
confidence: 99%
“…[3][4][5][6][7] This might indicate that insulin resistance precedes the rise in blood pressure. However, to our knowledge no prospective study has demonstrated the predictive value of insulin resistance with respect to glucose metabolism for the development of hypertension.…”
Section: Introductionmentioning
confidence: 99%